The Intellectual Network of Mandailing and Haramayn Muslim Scholars in the Mid-19th and Early 20th Centuries - Mhd. Syahnan; Asrul Asrul; Ja'far Ja'far (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
This paper attempts to study the scholars’ network of Mandailing and Haramayn Ulama in the mid-19th and early 20th centuries. By employing the content analysis method, it was discovered that the Mandailing scholars had made intellectual encounters with those in Haramayn, and some even established networks with the Egyptians and Indians. The Mandailing scholars connote those that ethnically originated from the Mandailing clan, and data reveals that they come from Tapanuli and East Sumatera residencies, both of which are parts of the modern era North Sumatera province. This information does deny that some of these scholars were born in Makkah. During the duration evaluated by the study, it was observed that some scholars studied religion intensively and settled in Makkah, while others only learned Islam by meeting the scholars in this region during the Hajj period. The last group of scholars studied religion intensely in Nusantara, but while performing hajj, they met the scholars and learned Islam in a very limited time. Mandailing scholars studied Islamic sciences, especially Quranic exegeses, hadīth, and Sufism, and taught them to several scholars from Arab and Nusantara. These scholars include Ahmad Khatib al-Minangkabawi, ‘Abd al-Qadir b. Shabir al-Mandili (Nasution), and Hasan Masysyath. Ideologically, they studied Islamic sciences in the context of the Sunnī school of thought, especially Ash‘ariyya and Shāfi‘iyya.